Managing Household Hazardous Waste in Malaysia: Legal, Fiqh and Climate Perspectives - Intan Nadia Ghulam Khan; Izawati Wook; Mashitah Abdul Mutalib; Nabilah Yusof @ Abdul Rahman; Hasnizam Hashim; Haliza A Shukor (Usuli Faqih Research Centre PLT, 2025)
Non-Indexed Publication